International Experience of Islamic Financial Organizations - Sattarova Dilfuza Dilshodbekovna (Zien Journals, 2022)
The article describes the foreign experience of Islamic financial organizations. In particular, thearticle discusses the current state of Islamic financial indicators of the leading countries in the field ofIslamic finance, the specific features of the activities of Islamic financial organizations in the CIS countriesare shown.
Keywords: Islamic finance, Gulf Cooperation Council, Commonwealth of Independent States, sukuk, Islamic FinTech, TakTech, roadmaps, the financial performance indi